Behavioral, perceptual, and neural alterations in sensory and multisensory function in autism spectrum disorder. (November 2015) - Baum, Sarah H.; Stevenson, Ryan A.; Wallace, Mark T.
Highlights: Although sensory processing problems are common in ASD, they are poorly characterized. There is increasing recognition of the prevalence and importance of multisensory processing changes in ASD. Sensory and multisensory representations form the building blocks of higher-order cognitive representations. Hence low-level sensory changes in ASD are likely to impact domains such as social communication. Remediation approaches that focus on sensory function may hold promise in ASD treatment. Abstract: Although sensory processing challenges have been noted since the first clinical descriptions of autism, it has taken until the release of the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) in 2013 for sensory problems to be included as part of the core symptoms of autism spectrum disorder (ASD) in the diagnostic profile. Because sensory information forms the building blocks for higher-order social and cognitive functions, we argue that sensory processing is not only an additional piece of the puzzle, but rather a critical cornerstone for characterizing and understanding ASD. In this review we discuss what is currently known about sensory processing in ASD, how sensory function fits within contemporary models of ASD, and what is understood about the differences in the underlying neural processing of sensory and social communication observed between individuals with and without ASD. In addition to highlighting the sensory features associated with ASD, we also emphasize the importance of multisensory processing in building perceptual and cognitive representations, and how deficits in multisensory integration may also be a core characteristic of ASD.